2018
DOI: 10.1140/epjc/s10052-018-6248-4
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative moduli stabilisation in type IIB/F-theory framework

Abstract: We propose a new mechanism of (geometric) moduli stabilisation in type IIB/F-theory four-dimensional compactifications on Calabi-Yau manifolds, in the presence of 7-branes, that does not rely on non-perturbative effects. Complex structure moduli and the axion-dilaton system are stabilised in the standard way, without breaking supersymmetry, using 3-form internal fluxes. Kähler class moduli stabilisation utilises perturbative string loop corrections, together with internal magnetic fields along the D7-branes wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 64 publications
(135 citation statements)
references
References 48 publications
4
131
0
Order By: Relevance
“…This vacuum breaks supersymmetry since for constant superpotential the Fauxiliary component of the volume modulus superfield does not vanish, unlike KKLT [4] but similar to the large volume scenario (although for a different reason) [5,6]. In [7], we have shown that this minimum can be uplifted to positive energy when appropriate D-term contributions from the D7-branes are taken into account. Here, we will analyse again these contributions and make a quantitative argument for the existence of perturbative dS vacua at large volume and weak string coupling.…”
Section: D-terms and De Sitter Vacuamentioning
confidence: 79%
See 4 more Smart Citations
“…This vacuum breaks supersymmetry since for constant superpotential the Fauxiliary component of the volume modulus superfield does not vanish, unlike KKLT [4] but similar to the large volume scenario (although for a different reason) [5,6]. In [7], we have shown that this minimum can be uplifted to positive energy when appropriate D-term contributions from the D7-branes are taken into account. Here, we will analyse again these contributions and make a quantitative argument for the existence of perturbative dS vacua at large volume and weak string coupling.…”
Section: D-terms and De Sitter Vacuamentioning
confidence: 79%
“…The interesting fact now is that the F-term potential has two distinct parts, both with the same power dependence but one of the two proportional to log(τ ) [7,26]:…”
Section: Corrections To the Kähler Potential And Runaway Moduli Behavmentioning
confidence: 99%
See 3 more Smart Citations